Xanthoma of the temporal bone. A case report - Salazar Minaya, Ray (2021)
We present the case of a 53-year-old female patient who presented with one-year history of mixed frequency tinnitus of the left ear and sudden development of unilateral deafness. She received treatment with oral steroids plus intratympanic infiltrations. Imaging studies using CT-Scan and MRI disclosed a solid tumor of well-defined borders in the union of the petrosal and squamous portions of the left temporal bone. A mastoidectomy was performed, the anatomopathological studies revealed a xanthoma of the temporal bone. A literature review was performed.